The determinants of the tourist traffic in the castle’s museum of Malbork - Parzych, Krzysztof (Journal of Education, Health and Sport, 2016)
The aim of his article was an analysis of the tourist traffic and tourist perceptron of the castle’s museum of Malbork. As a tourist destination. For his purpose was made an analysis of the tourist traffic Fasing on the investigations results connected with analysis of statistic data. As the source of the data for the analysis of the research problem was used results of the research of the tourist migrations made in the castle’s museum in Malbork in the holiday season of the 2010 year. Besides it for the charactersitic of the research problem was used results of questionnaire made between tourists visiting museum of the castle in the time of the holiday season of 2010 year. In the article was made an analysis of the tourist traffic in years 1959-2010.